PET-CT imaging of Carcinoma of the Oesophagus: The Kwa-Zulu Natal perspective - Mpikashe, Pilisiwe; Nyakale, Nozipho (Eastern Journal of Medical Sciences, 2018)
The introduction of computer software which enables assessment of various metabolic parameters has added value to the imaging, diagnosis and prognosis of oesophageal carcinoma (OC). Positron emission tomography/Computed tomography     (PET/CT) is an imaging modality used for monitoring and follow-up of patients with flourodeoxyglucose (FDG) avid lesions in OC. The association of HIV with OC remains controversial, however in Kwa-Zulu Natal (KZN), where the incidence of this infection is high, the role of PET/CT in predicting the prognostic outcome of OC is important and may provide further information that may alter treatment.